PENGATURAN BILLING HOTSPOT PADA SISTEM JARINGAN RT/RW NET DENGAN MIKROTIK ROUTER OS - Danang Danang; Kenny Setiawan (Jurnal Publikasi Teknik Informatika, 2022)
This research is oriented to the Design of RT/RW Net Hotspot System With Mikrotik RouterOS as Billing Management, where previously Delta Net was a cable-based internet cafe where users could only enjoy internet access after visiting Delta Net. With the hotspot system, it is hoped that users will be facilitated in terms of getting internet access without having to leave their homes and Delta Net can survive in the midst of the growing number of internet cafe businesses. From the problems that exist in Delta Net in terms of limited internet access for users who want to be able to enjoy easy internet access without having to leave home and the growing internet cafe business, the use of a hotspot system in the RT / RW environment as a means to facilitate users who want to get access easy internet without having to leave the house and as a means to remain competitive in the midst of the development of the cafe business, so that both users and cafe owners can benefit from the hotspot system